Modified natural rubber adhesive as well as adhesive tape and preparation method thereof

Through blending and initiator treatment of natural rubber with hydroxyethyl methacrylate, rosin resin and lac resin, the polarity and adhesion of the tape are improved, and combined with regenerated polyester recovery material and graft polymer, the solution is solved The problems of insufficient polarity and poor environmental performance of the tape have achieved high-performance, green and environmentally friendly tape preparation.

CN119161836APending Publication Date: 2024-12-20NINGBO SOKEN CHEM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411499611.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The polarity of natural rubber in existing tapes is small, resulting in poor bonding performance with polar substrate or patches. The existing improved methods such as grafting or adding natural resins have environmental protection and performance stability problems. .

Method used

By blending natural rubber with hydroxyethyl methacrylate, rosin resin and lac resin, and using dibenzoyl peroxide initiator to generate active free radicals, the natural rubber undergoes double bond grafting and improves its polarity. And recycled polyester recovery material and maleic anhydride grafted polypropylene are used in the substrate layer to enhance the adhesiveness and stability of the tape.

Benefits of technology

It significantly improves the polarity and adhesion of natural rubber, enhances the bonding performance between tape and polar materials, and realizes green and environmentally friendly tape preparation through the use of recycled materials and environmentally friendly functional bodies, and improves the biomass of tape Carbon content and performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a modified natural rubber adhesive as well as an adhesive tape and a preparation method thereof. The modified natural rubber adhesive comprises the following components in parts by mass: 100 parts of natural rubber, 5-15 parts of hydroxyethyl methylacrylate, 5-15 parts of rosin resin, 5-15 parts of shellac resin, 3-5 parts of an initiator, 200-400 parts of a solvent and 1-2 parts of a curing agent. Compared with the prior art, the polarity of the natural rubber can be greatly improved, the adhesion and compatibility between the natural rubber and a polar material are improved, fitting with a base material is facilitated, the situation that the adhesive force is too low is avoided, and the performance stability of the adhesive tape can be better; and recycling of waste materials, leftover materials and the like in the production and processing process is achieved, and the green and environment-friendly requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adhesive tapes, and in particular to a modified environmentally friendly adhesive, an adhesive tape and a preparation method thereof. Background Art

[0002] In tape products, the adhesive can use natural rubber as the main body, and its main component is polyisoprene, for example, the Chinese invention patent with application number CN202311365741.5 (publication number CN117417703A), the Chinese invention patent with application number CN202211702132.X (publication number CN115873530A), etc. However, since the polarity of natural rubber is relatively small, the bonding performance with polar substrates or polar adherends is poor, and it is usually necessary to increase the polarity of natural rubber by grafting acrylic monomers to natural rubber or adding some natural resins. However, both methods have certain defects. Among them, the former introduces petrochemical raw materials, which is not in line with the development direction of environmental protection, and the latter is only a simple physical mixing, and many natural resins and natural rubbers have large differences in polarity, which are easy to disperse unevenly, resulting in poor performance stability.

[0003] Furthermore, we should actively adopt new green and environmentally friendly functional materials, increase the use of recycled plastics that meet quality control standards and use control requirements, strengthen the research and development of recyclable, easily recyclable and degradable alternative materials and products, reduce application costs, and effectively increase the supply of green products. At the same time, it is also specifically mentioned that we should strengthen scientific and technological support, increase the key core technology research and results transformation of recyclable materials, and improve the performance of alternative materials and products. Summary of the invention

[0004] The first technical problem to be solved by the present invention is to provide a modified natural rubber adhesive with high polarity, high stability, high biomass carbon content and good viscosity in view of the existing technology.

[0005] The second technical problem to be solved by the present invention is to provide a green and environmentally friendly adhesive tape using the modified natural rubber adhesive according to the prior art.

[0006] The third technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned adhesive tape in view of the prior art.

[0007] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a modified natural rubber adhesive, characterized by comprising the following components and their mass fractions:

[0008]

[0009] Furthermore, the initiator is dibenzoyl peroxide (BPO) and the solvent is toluene.

[0010] Furthermore, the curing agent is at least one of toluene diisocyanate, diphenylmethane diisocyanate or hexamethylene diisocyanate.

[0011] The technical solution adopted to further solve the above second technical problem is: an adhesive tape, including an adhesive layer, characterized in that the adhesive layer adopts the modified natural rubber adhesive as described above.

[0012] Furthermore, it also includes a substrate layer, at least one side of which is coated with the modified natural rubber adhesive to form the adhesive layer, and the substrate of the substrate layer includes the following components and their mass fractions:

[0013]

[0014] The polyester recycled material is recycled polyester (rPET, polyethylene terephthalate), which is waste and scraps generated during the production and processing process, and is subsequently reused through melt granulation.

[0015] Furthermore, the compatibilizer is maleic anhydride grafted polypropylene, which has the functions of improving the compatibility between calcium carbonate and the matrix and enhancing toughness.

[0016] Furthermore, the plasticizer is at least one of dioctyl phthalate, dioctyl phthalate, dibutyl phthalate or diethyl phthalate.

[0017] Furthermore, it also includes a release film, which includes the above-mentioned substrate layer and a release agent coated on the substrate layer, the components of the release agent include polymethylvinylsiloxane and polymethylhydrogensiloxane, and the coating amount is 0.1-0.3g / m 2 .

[0018] The technical solution adopted to further solve the third technical problem is: a method for preparing the adhesive tape as described above, characterized in that it comprises the following steps:

[0019] (1) Preparation of substrate layer:

[0020] The polyester recycled material, calcium carbonate powder, compatibilizer and plasticizer are added into a single screw extruder according to the above mass proportions, heated and melted, and extruded, and a sheet press is used to form a thick sheet, and a polyester film material is formed by biaxial stretching;

[0021] (2) Preparation of modified natural rubber adhesive:

[0022] (a) adding the above-mentioned mass parts of natural rubber, rosin resin and shellac resin into a certain mass of solvent, heating and stirring until all components are completely dissolved;

[0023] (b) adding hydroxyethyl methacrylate to the mixed solution according to the above mass fractions, and stirring for 5 to 10 minutes;

[0024] (c) adding the initiator to the remaining solvent in the above-mentioned mass fraction to prepare an initiator solution;

[0025] (d) adding the initiator solution to the mixed solution and reacting for 4 to 6 hours;

[0026] (e) cooling and filtering the discharged material to obtain an uncured modified natural rubber adhesive solution;

[0027] (f) before applying the tape, adding a curing agent to the modified natural rubber adhesive solution and stirring for 20 to 30 minutes to obtain a modified natural rubber adhesive;

[0028] (3) Preparation of tape:

[0029] The modified natural rubber adhesive prepared above is evenly coated on the release film with a coating thickness of 1 to 100 μm, dried at 50 to 120° C. for 1 to 5 minutes, and then laminated with one side of the substrate layer prepared above to obtain a single-sided tape;

[0030] Alternatively, the modified natural rubber adhesive is evenly coated on a release film with a coating thickness of 1 to 100 μm, dried at 50 to 120° C. for 1 to 5 minutes, and then laminated with the other side of the substrate layer prepared above to obtain a double-sided tape.

[0031] Furthermore, the stirring process in step (a) is carried out in a N2 atmosphere, the heating temperature is 80°C, and the stirring rate is 300r / min.

[0032] Compared with the prior art, the advantages of the present invention are: in the present invention, by blending natural rubber with functional bodies such as hydroxyethyl methacrylate, rosin resin and shellac resin, the active free radicals generated by the initiator are used to open and rebond the unsaturated double bonds between the natural rubber and the functional body, thereby realizing double bond grafting. Among them, by introducing strongly polar side groups (such as -OH and -COOH, etc.) into the natural rubber main chain, the polarity of the natural rubber is greatly improved, and the adhesion and compatibility between it and the polar material are improved, which is conducive to the bonding with the substrate and avoids too low adhesion. Moreover, compared with the prior art (rosin resin is directly added in the form of filler during the preparation of the adhesive to improve the adhesion), the performance stability of the tape is better through grafting. In addition, the substrate layer in the present invention uses polyester recycled materials, which realizes the recycling and reuse of waste materials, scraps, etc. in the production and processing process, and meets the requirements of green environmental protection.

[0033] Furthermore, in the present invention, hydroxyethyl methacrylate, natural rosin resin and shellac resin are selected as modified functional bodies, and the polarity of the modified natural rubber adhesive can be adjusted according to the content of hydroxyethyl methacrylate, rosin resin and shellac resin, thereby greatly improving the application range of the tape. Specifically, hydroxyethyl methacrylate mainly introduces hydroxyl groups as bridging points for subsequent action with isocyanate curing agents; natural rosin resin has abundant carboxyl groups that can increase the viscosity of the modified natural rubber adhesive, thereby improving the wettability of contact with the substrate; and shellac resin contains the structure of hydroxy fatty acids and hydroxy sesquiterpene acids, which can introduce more hydroxyl groups, which is beneficial to the curing reaction, and can replace a part of hydroxyethyl methacrylate, which can effectively increase the biomass carbon content of the tape. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below with reference to the embodiments.

[0035] The modified natural rubber adhesive of the present invention comprises the following components and their weight fractions:

[0036] 100 parts of natural rubber, 5-15 parts of hydroxyethyl methacrylate, 5-15 parts of rosin resin, 5-15 parts of shellac resin, 3-5 parts of initiator, 200-400 parts of solvent, 1-2 parts of curing agent. The initiator is dibenzoyl peroxide (BPO), the solvent is toluene, and the curing agent is at least one of toluene diisocyanate, diphenylmethane diisocyanate or hexamethylene diisocyanate.

[0037] Furthermore, the natural rubber used was purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 9006-04-6; the rosin resin used was purchased from Zhejiang Xinsong Resin Co., Ltd., model S7090P; and the shellac resin used was purchased from Shandong Xintu Chemical Co., Ltd., CAS No. 9000-59-3.

[0038] The substrate in the present invention includes the following components and their mass fractions:

[0039] 100 parts of polyester recycled material, 3-5 parts of calcium carbonate powder, 4-8 parts of compatibilizer, and 0-4 parts of plasticizer.

[0040] The polyester recycled material is recycled polyester (rPET, polyethylene terephthalate), which is waste and scraps generated during the production and processing of the applicant, and is subsequently reused through melt granulation. The compatibilizer is maleic anhydride grafted polypropylene, which has the functions of improving the compatibility of calcium carbonate and the matrix and toughening. The plasticizer is at least one of dioctyl phthalate, dioctyl phthalate, dibutyl phthalate or diethyl phthalate.

[0041] The preparation method of the adhesive tape of the present invention is specifically as follows:

[0042] (1) Preparation of substrate layer:

[0043] The polyester recycled material, calcium carbonate powder, compatibilizer and plasticizer are added into a single screw extruder according to the above mass proportions, heated and melted for extrusion, and made into thick sheets by a sheeting machine, and then biaxially stretched to form a polyester film material.

[0044] (2) Preparation of modified natural rubber adhesive:

[0045] (a) adding natural rubber, rosin resin and shellac resin according to the above mass fractions to a certain mass of solvent, heating and stirring until all components are completely dissolved; and the stirring process is carried out in a N2 atmosphere, the heating temperature is 80°C, and the stirring rate is 300r / min.

[0046] (b) Add hydroxyethyl methacrylate into the mixed solution according to the above mass fractions and stir for 5 to 10 minutes.

[0047] (c) adding the initiator to the remaining solvent (the amount of solvent here plus the amount of solvent used in step (a) is the total amount of solvent) according to the above-mentioned mass fraction to prepare an initiator solution, which is a freshly prepared solution with a concentration of 10%.

[0048] (d) Adding the above initiator solution to the above mixed solution and reacting for 4 to 6 hours at a reaction temperature of 80°C.

[0049] (e) cooling and filtering the material to obtain an uncured modified natural rubber adhesive solution.

[0050] (f) before applying the tape, a curing agent is added to the modified natural rubber adhesive solution, and the solution is stirred at room temperature for 20 to 30 minutes to obtain a modified natural rubber adhesive.

[0051] (3) Preparation of tape:

[0052] The modified natural rubber adhesive prepared above is evenly coated on the release film with a coating thickness of 1 to 100 μm, so that the coated surface does not contact the conductive shaft, dried at 50 to 120° C. for 1 to 5 minutes, and then compounded with one side of the substrate layer prepared above to obtain a single-sided tape.

[0053] Alternatively, the modified natural rubber adhesive is evenly coated on a release film with a coating thickness of 1 to 100 μm, so that the coated surface does not contact a conductive shaft, dried at 50 to 120° C. for 1 to 5 minutes, and then laminated with the other side of the substrate layer prepared above to obtain a double-sided tape.

[0054] The release film of the present invention comprises the above-mentioned substrate layer and a release agent (produced by Shin-Etsu Chemical Co., Ltd., Japan, trade name: KM-3951) coated on the substrate layer, wherein the release agent comprises polymethylvinylsiloxane and polymethylhydrogensiloxane, and the coating amount is 0.1 to 0.3 g / m 2 The modified natural rubber adhesive can be coated by knife edge, anilox roller, DIE and other coating methods.

[0055] The specific formulas of the adhesives in the embodiments and comparative examples are shown in Table 1, and the performance tests of the adhesive tapes prepared in the embodiments and comparative examples are carried out. The performance test results are shown in Table 1. The amounts of the substances in Table 1 without indicating the units are all parts by weight.

[0056] The test method in this embodiment is as follows:

[0057] 1. Adhesion

[0058] Test equipment: Tensile testing machine: Constant speed tensile tensile testing machine, equipped with recorder or computer software.

[0059] Laminating device: Steel roller with rubber coating on the surface, weighing 2kg, with handle, and capable of reciprocating motion.

[0060] Test plate: mirror steel plate (plate B).

[0061] Test piece: Cut a 25 mm wide test piece from the pre-treated test piece.

[0062] Test environment: 23℃, 50%RH.

[0063] Test method: Wipe the test board clean with IPA and place it in an environment of 23°C, 50% RH for more than 2 hours; stick the test piece on the test board and roll it back and forth 3 times with a 2kg rubber roller. After placing it in the test environment for 20 minutes, use a tensile testing machine to test the peel strength of the test piece at ∠180°. The peel speed is 300mm / min and the peel length is more than 100mm. The same sample is measured twice in parallel.

[0064] 2. Retention

[0065] Test equipment: Dryer: A forced air dryer capable of maintaining a constant temperature of 40°C.

[0066] Laminating device: Steel roller with rubber coating on the surface, weighing 2kg, with handle, and capable of reciprocating motion.

[0067] Test plate: SUS304 stainless steel test plate.

[0068] Test piece: Cut a 20 mm wide test piece from the pre-treated test piece.

[0069] Test environment: 40℃ constant temperature environment.

[0070] Test method: After polishing the test board, wipe it clean with ethyl acetate and place it in an environment of 23℃50%RH for more than 2 hours. Using the lower edge of the polished surface of the test board as the reference, paste the test piece on the test board with a bonding area of ​​20×20mm 2 Then, use a rubber roller to roll back and forth ten times, draw a line on one end of the test piece (the end attached to the test plate), and then place it in a blast dryer that can maintain 40°C. After 20 minutes, start hanging a 1kg weight for testing. If it does not fall after 1hr, test its distance from the origin in 0.1mm. If it falls, record the time of falling. Parallel measurements are performed twice.

[0071] 3. Initial adhesion

[0072] Test equipment: Initial adhesion device: The tilt angle is 30°.

[0073] Rolling ball: The material is high carbon chromium bearing steel, and the steel ball is cleaned with ethyl acetate. The ball reading is based on the inch diameter of the ball.

[0074] Test piece: Cut a 20 mm wide test piece from the pre-treated test piece.

[0075] Test environment: 23℃, 50%RH.

[0076] Test method: The adhesive surface of the test piece is about 120mm or more in length. The adhesive surface is fixed upward at the specified position of the inclined plate, and a polyester film for walking is glued on it, and a layer of the tape is placed under the polyester film. The ball starts to roll from 100mm above the upper end of the walking part. In the test section, the largest ball that can stop rolling is tested twice in parallel with the same sample.

[0077] Table 1 shows the formula composition and test results of each embodiment and comparative example

[0078]

[0079] As shown in Table 1, too high a content of hydroxyethyl methacrylate and too low a content of rosin resin / shellac resin will result in a decrease in the ratio of biomass carbon / recycled carbon, thus failing to meet the requirement of >90%. In addition, not adding a curing agent or too low a content of hydroxyethyl methacrylate will result in a low holding force of the tape, resulting in the phenomenon of falling off. When the total resin addition amount is controlled to be the same (rosin + shellac), using shellac resin instead of rosin resin can effectively improve the holding force as expected.

Claims

1. A modified natural rubber adhesive, characterized in that Includes the following components and their mass fractions:

2. The modified natural rubber adhesive according to claim 1, characterized in that: The initiator is dibenzoyl peroxide.

3. The modified natural rubber adhesive according to claim 1, characterized in that: The curing agent is at least one of toluene diisocyanate, diphenylmethane diisocyanate or hexamethylene diisocyanate.

4. An adhesive tape comprising an adhesive layer, characterized in that: The adhesive layer adopts the modified natural rubber adhesive as described in any one of claims 1 to 3.

5. The adhesive tape according to claim 4, characterized in that It also includes a substrate layer, at least one side of which is coated with the modified natural rubber adhesive to form the adhesive layer, and the substrate of the substrate layer includes the following components and their mass fractions:

6. The adhesive tape according to claim 5, characterized in that The compatibilizer is maleic anhydride grafted polypropylene.

7. The adhesive tape according to claim 5, characterized in that The plasticizer is at least one of dioctyl phthalate, dioctyl phthalate, dibutyl phthalate or diethyl phthalate.

8. The adhesive tape according to claim 5, characterized in that The invention also comprises a release film, which comprises the substrate layer and a release agent coated on the substrate layer, wherein the components of the release agent include polymethylvinylsiloxane and polymethylhydrogensiloxane.

9. A method for preparing an adhesive tape as claimed in any one of claims 5 to 8, characterized in that The following steps are involved: (1) Preparation of substrate layer: Add the polyester recycled material, calcium carbonate powder, compatibilizer and plasticizer according to the above mass parts into a single screw extruder, heat and melt, extrude, press into a thick sheet, and then make a polyester film material by biaxial stretching; (2) Preparation of modified natural rubber adhesive: (a) adding the above-mentioned mass parts of natural rubber, rosin resin and shellac resin into a certain mass of solvent, heating and stirring until all components are completely dissolved; (b) adding hydroxyethyl methacrylate to the mixed solution according to the above mass fractions, and stirring for 5 to 10 minutes; (c) adding the initiator to the remaining solvent according to the above mass fraction to prepare an initiator solution; (d) adding the initiator solution to the mixed solution and reacting for 4 to 6 hours; (e) cooling and filtering the material to obtain an uncured modified natural rubber adhesive solution; (f) before applying the tape, adding a curing agent to the modified natural rubber adhesive solution and stirring for 20 to 30 minutes to obtain a modified natural rubber adhesive; (3) Preparation of tape: The modified natural rubber adhesive prepared above is evenly coated on the release film with a coating thickness of 1 to 100 μm, dried at 50 to 120° C. for 1 to 5 minutes, and then laminated with one side of the substrate layer prepared above to obtain a single-sided tape; Alternatively, the modified natural rubber adhesive is evenly coated on a release film with a coating thickness of 1 to 100 μm, dried at 50 to 120° C. for 1 to 5 minutes, and then laminated with the other side of the substrate layer prepared above to obtain a double-sided tape.

10. The method for preparing the adhesive tape according to claim 9, characterized in that: The stirring process in step (a) is carried out in a N2 atmosphere, with a heating temperature of 80°C and a stirring rate of 300 r / min.

Citation Information

Patent Citations

  • Natural rubber pressure-sensitive adhesive, preparation process thereof and adhesive tape

    CN115873530A

  • BOPP (biaxially-oriented polypropylene) adhesive tape with ultrahigh viscosity and high heat resistance as well as preparation method and preparation system of BOPP adhesive tape

    CN117417703A